Science World [motion pictures] Ecology : grasslands; - gropical rain forest; - desert; - tundra. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 13:Grasslands; - Tropical rain forest; - Desert; - Tundra
Original copy in VHS format (VHS 14)
[Distributed by] International Book Center, Philippines
Keywords: Grasslands; Deserts; Tundra; Rain Forests